Rationalizing presidential vacancy due to permanent moral incapacity - Campos Bernal, Heber Joel (2025)
This article deals with the figure of the presidential vacancy due to the cause of permanent moral incapacity. In this sense, it maintains that it operates, in fact, as a kind of informal political trial due to the limitations of article 117 of the Constitution that prevents that the president could be accused during his mandate outside of four extraordinary assumptions. Thus, it proposes that if it is not possible to amend the Constitution on this point, it is decided to rationalize the presidential vacancy in order to respect the right to due process of the president, and limit the discretion of the Congress.